Peak Voltage Measurements Using Standard Sphere Gap Method. (8th October 2014) - Ungureanu, Constantin; Nemțoi, Lăcrămioara Mihaela
Abstract : The paper presents a measurement system of peak value of high voltage (H.V.) using 150 mm diameter sphere gap, disposed in vertical position. Experimental breakdown results have been compared with standard values at atmospheric reference conditions STC (20°C, 101.3 kPa, or 760 mmHg). The main experimental and theoretical characteristics are presented.